Pengaruh Kurs Rupiah Terhadap Indeks Harga Saham (Studi Pada Indeks Saham Syariah Indonesia Periode 2011-2013) - Imam Dwi Saputra; Leo Herlambang (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Sensitivity of stock market is appeared when the domestic currency exchange rate fluctuations happened. Uncontrolled currency fluctuations will affect the performance of capital market entities which have an impact on stock price movement. This thesis is to determine the effect of exchange rate on ISSI stock price index in the 2011-2013 periods.This thesis uses a quantitative approach to analyze secondary data whichrepresented by exchange rate and ISSI stock price index. Those values are monthly data over the period 2011-2013. This thesis also uses a significance level of 5%.The regression result in this thesis indicates that the exchange rate variable has a significant effect partially on ISSI stock price index in the 2011-2013 periods. REFERENCES Boediono. 2005. Seri Sinopsis Pengantar Ilmu Ekonomi No 3 : Ekonomi Internasional. Edisi Pertama. Yogyakarta: PT BPFEJogiyanto, HM. 2009. Teori Portofolio dan Analisis Investasi. Edisi Keenam. Yogyakarta: PT BPFEKismono, Gugup. 2001. Pengantar Bisnis. Edisi Pertama. Yogyakarta: PT BPFENugraha, Adit Tia. 2013. Analisis Pengaruh SBI, Kurs Rupiah, Harga Emas Dunia, Indeks Hang Seng, dan Indeks Nikkei 225 terhadap IHSG (Studi Kasus Bursa Efek Indonesia Periode 2008-2011). Skripsi tidak diterbitkan. Jakarta Fakultas Ekonomi UIN Syarif HidayatullahShihab, Quraish. 2009. Tafsir Al Mishbah Volume 6. Jakarta: Lentera HatiSugiyono. 2011. Statistika untuk Penelitian. Bandung: AlfabetaSukirno, Sadono. 2004. Makroekonomi Teori Pengantar. Edisi Ketiga. Jakarta: Rajawali PersTriyono. 2008. Analisis Perubahan Kurs Rupiah Terhadap Dollar Amerika. Jurnal Ekonomi Pembangunan. Vol 9 No 2. Desember 2008: 156-167. Universitas Muhammadiyah Surakartawww.bi.go.idwww.idx.co.id